The Role of Nursing in Ruptured Gastrointestinal Stromal Tumor in Adolescents and Young Adults: A Case Report - Alhazmy, Riham Saud; Baghdadi, Ayman (Archives of Clinical and Medical Case Reports, 2024)
Gastrointestinal stromal tumors (GISTs) are rare life-threatening forms of cancer representing 0.1%-3% of all gastrointestinal (GI) malignancies. Nursing has become a critical component in handling patients with gastrointestinal tumors. This case report investigates the role of nursing in ruptured GISTs in adolescents and young adults (AYA). It focuses on a 17-year-old female who was admitted to the emergency department (ER) due to the sudden onset of generalized abdominal pain, nausea, and vomiting. After an initial examination, the patient underwent an urgent laparotomy. During this procedure, an unexpected ruptured cystic outgrowth was found originating from the distal ileum. Resection and an anastomosis of the affected section were performed, and a pelvic drain was inserted. GISTs are malignant mesenchymal tumors of the gastrointestinal tract. In rare cases, the tumor may rupture and result in hemoperitoneum; thus, it is challenging for healthcare workers to detect and manage it.